Organic Fraction of Municipal Solid Waste: Overview of Treatment Methodologies to Enhance Anaerobic Biodegradability - Paritosh, Kunwar; Yadav, Monika; Mathur, Sanjay; Balan, Venkatesh; Liao, Wei; Pareek, Nidhi; Vivekanand, Vivekanand (Frontiers in Energy Research, 2018)
Organic fraction of municipal solid waste and its proper disposal is becoming a serious challenge around the world. Environmental pollution, public health risk, and scarcity of dumping land are the aftereffects of its improper disposal. Embodied energy recovery associated with the organic waste along with waste minimization may be achieved using anaerobic digestion. The chemical composition of the substrate plays a crucial role among the factors responsible for digestion performance and cumulative methane production. Treatment of substrate to enhance the digestion performance is gaining momentum in the recent years. This review provides an overview of different treatment methodologies including mechanical, thermal, chemical, biological, ultrasonic, and microwave approaches to enhance methane yield of anaerobic digestion of organic fraction of municipal solid waste (OFMSW). Environmental impact analysis of treatment techniques, along with comparison of treatment methodologies and techno-economic assessment, has also been discussed to provide a proper insight into the various processing methods.